2020
DOI: 10.3389/fonc.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Embryonic Leucine Zipper Kinase Promotes Tumor Growth and Metastasis via Stimulating FOXM1 Signaling in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a common gastrointestinal malignancy and is one of the most important cause of cancer related mortalities in the world. However, there is no clinically effective targeted therapeutic drugs for ESCC due to lack of valuable molecular therapeutic targets. In the present study, we investigated the biological function and molecular mechanisms of maternal embryonic leucine zipper kinase (MELK) in ESCC. The expression of MELK mRNA and protein was determined in cell lines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 51 publications
(84 reference statements)
0
44
0
Order By: Relevance
“…Another potential way that Mycoplasmas have to influence cancer formation, is by deregulating expression of Bone morphogenetic protein 2 (BMP2), which is an essential growth factor and morphogen, implicated in cancer promotion and growth [ 158 , 159 ]. In fact, it has been shown that infection by Mycoplasma penetrans , Mycoplasma fermentans, and Mycoplasma hominis induces BMP2 RNA expression, as well as secretion of mature BMP2 protein, in cells that usually do not express such protein, including BEAS-2B cells (immortalized human bronchial epithelial cells), A549 cells (lung adenocarcinoma cells), plus several other cell lines of different origins (mesenchymal, epithelial, and myeloid).…”
Section: Mycoplasmas and Cancermentioning
confidence: 99%
“…Another potential way that Mycoplasmas have to influence cancer formation, is by deregulating expression of Bone morphogenetic protein 2 (BMP2), which is an essential growth factor and morphogen, implicated in cancer promotion and growth [ 158 , 159 ]. In fact, it has been shown that infection by Mycoplasma penetrans , Mycoplasma fermentans, and Mycoplasma hominis induces BMP2 RNA expression, as well as secretion of mature BMP2 protein, in cells that usually do not express such protein, including BEAS-2B cells (immortalized human bronchial epithelial cells), A549 cells (lung adenocarcinoma cells), plus several other cell lines of different origins (mesenchymal, epithelial, and myeloid).…”
Section: Mycoplasmas and Cancermentioning
confidence: 99%
“…As one of the most common pathohistological subtypes of ESCC, ESCC usually composes over 90% of all EC cases in areas of Asia and Sub-Saharan Africa [ 1 , 3 ]. Despite the advances in diagnosis and treatment, ESCC still carries a poor prognosis [ 4 ], and the 5-year overall survival rate ranges from 15 to 25%[ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Features obtained from deep learning-based radiomics were combined with clinical parameters such as patient age, size of the lesion, Breast Imaging Reporting and Data System (BI-RADS) category, tumor type, estrogen receptor status, progesterone receptor status, human epidermal growth factor receptor 2 (HER2), Ki-67 proliferation index, and others. Sun et al [ 59 ] included additional molecular subtype information such as HER2-positivity and triple-negative status. Luminal and Liao et al [ 54 ] introduced a combination feature model of B-mode ultrasound images and strain elastography and showed better performance than those of models established using these two modalities alone.…”
Section: Diagnostic Support By Deep Learning Analyticsmentioning
confidence: 99%